The Influence of Macroeconomic Indicators on Foreign Exchange Reserves in Indonesia - Sukarniati, Lestari; Widara, Widara; Asmara, Gea Dwi (Journal of Economics Research and Social Sciences, 2025)
This study aims to analyze the influence of macroeconomic indicators such as exports, imports, inflation, exchange rates, and the Bank Indonesia (BI) rate on foreign exchange reserves in Indonesia during the 2010-2023 period. The research methodology employed is multiple linear regression analysis and the Error Correction Model (ECM) with monthly time series data. The results indicate that exports, inflation, and exchange rates significantly affect Indonesia's foreign exchange reserves in the long run. Exports and exchange rates have a positive effect, while inflation also positively affects foreign exchange reserves. Conversely, the benchmark interest rate (BI Rate) has a significant adverse impact. In the short term, only inflation and exchange rate have a significant effect, negatively impacting foreign exchange reserves. This research contributes original value to the literature by integrating a broad set of macroeconomic indicators into a single, comprehensive model. This approach is seldom found in previous studies. Whereas earlier research typically assessed these variables in isolation or limited combinations, this study concurrently examines their collective impact within a consistent ECM framework over a 14-year monthly dataset. As such, this study enhances the current understanding of the short- and long-term macroeconomic dynamics affecting foreign exchange reserves and provides valuable insights for policymakers in formulating external sector strategies.